Edukasi Waspada DBD dan Pandai Memilih Jajanan di Sekolah dengan Leaflet - Deni Setiawan; Hayatun Izma; Okta Mutia Sari; Nadya Rahmi; Nurul Savira Fahira; Dinna Fitria Kumala; Fitria Handayani (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Dengue Hemorrhagic Fever (DHF) is one of the most common diseases in regions such as Southeast Asia. The incidence of DHF infection is estimated to reach 50 to 100 million cases each year. Snacks or street food are usually presented in various colors, shapes, tastes, sizes to make it attractive to buyers. Data analysis by BPOM shows that as much as 40% of snacks are not in accordance with food safety. The two problems above can trigger extraordinary events (KLB), so it is important to do education to prevent this. The health promotion method used is by providing education to participants in the form of lectures and accompanied by the provision of leaflets. The results of the activity show an increase in the knowledge of educational participants based on the post-test results. Health promotion activities (Promkes) about DHF and Pinter choosing snacks at school using effective leaflets to increase participants' knowledge. This increase in knowledge is expected to prevent outbreaks due to DHF and food poisoning.